Tingkat Kepuasan Konsumen pada Affogato by Elle Gelato Cafe di Kelurahan Malalayang Satu Kota Manado - Pangerapan, Jhersy Galvin Axel; Baroleh, Jenny; Tarore, Melissa Lady Gisela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
This study aims to analyze the level of consumer satisfaction at Affogato by Elle Gelato Café. The research employed a quantitative descriptive method, collecting data through questionnaires distributed to 40 respondents. The data were analyzed using the Customer Satisfaction Index (CSI) approach to determine the overall level of customer satisfaction. The calculation results show that the CSI score is 94.66%, which falls into the “Satisfied” category. These findings indicate that the majority of consumers feel that the quality of service and products provided has met or even exceeded their expectations. The highest satisfaction scores were found in the service aspect, such as staff friendliness and appearance, and in the product aspect, particularly taste and portion size. Meanwhile, the promotion aspect received the lowest score among the five variables, especially in terms of sales promotions and promotional media, although it still falls within the "Satisfied" category. In conclusion, Affogato by Elle Gelato Café has successfully created a positive experience for its customers through high-quality service and products. However, improvements in promotional strategies are needed to more effectively attract and retain consumer interest.